Effects of medicine ball mass on the intensity of 90°/90° plyometric throwing exercise. (November 2019) - Riemann, Bryan L.; Hipko, Nick; Johnson, Wayne; Murphy, Thomas; Davies, George J.
Abstract: Objectives: To quantify the effects of medicine ball mass (1 kg, 1.5 kg, 2 kg) on the intensity of 90°/90° plyometric throwing exercise. Study design: Controlled laboratory study. Setting: Biomechanics laboratory. Participants: Fifteen physically active collegiate aged men. Main outcome measures: Kinematics of the upper extremity were collected during completion of eight to ten repetitions of 90°/90° plyometric throwing exercise with three different mass medicine balls. Four parameters, medicine ball release and contact momentum, time-to-rebound, and contact time, were computed for each selected repetition and used for statistical analysis. Results: Ball mass did not significantly influence time-to-rebound (P = .718) and had a small (less than 0.05s) effect on ball contact time (P = .039). Ball release momentum was significantly greater (P < .001, 67–123% greater) than ball contact momentum. Medicine ball mass significantly increased both ball release (34–35%) and ball contact (45–67%) momentum however the effect was significantly greater for ball release momentum (P = .005). Conclusions: These results document the effects of increasing medicine ball mass during 90°/90° plyometric throwing exercise and provide evidence for designing upper extremity plyometric training programs. Based on ball contact momentum being less than ball release momentum, as well as ball mass having greater influence on ball release velocity, we suggest that 90°/90° plyometric throwing exercise is a safe exercise. Highlights: The effects of ball mass on the intensity of 90°/90° plyometric throwing exercise were documented. Ball release momentum was greater than ball contact momentum, which supports the safety of the exercise. Results provide a foundation for future research to study 90°/90° plyometric throwing exercise in patients recovering from upper extremity pathology.